Implementasi Metode Talaqqi dalam Menghafal Alquran - Sania Sania; Ahmad Kosasih (An-Nuha, 2022)
This research was motivated by an interest in the implementation of the talaqqi method in memorizing the Qur'an at TPQ Baitul Rahmah Simpang III Patangan. This study aims to examine the implementation of the talaqqi method in memorizing the Koran, evaluating the talaqqi method in memorizing the Koran, and the inhibiting and supporting factors of the talaqqi method in memorizing the Koran. The method used in this research is qualitative research with a descriptive analysis approach and using field studies. The results showed that: First, the implementation of the talaqqi method was carried out by way of the students sitting in a circle and the teacher conveying directly to the students about the verse or letter that would be memorized correctly. Second, the evaluation of the talaqqi method was carried out without the knowledge of the students and was called randomly. Third, the inhibiting factor of the talaqqi method at TPQ Baitul Rahmah Simpang III Palanggaran, namely the students who feel bored while waiting in line because of the individual memorization deposits, the supporting factor for the talaqqi method at TPQ Baitul Rahmah Simpang III Palanggaran, namely the high interest of the students to learn the Qur’an.